АНАЛІЗ, СИНТЕЗ І СПІВСТАВЛЕННЯ З ІНШИМИ ДОКАЗАМИ ЯК СПОСОБИ ПЕРЕВІРКИ РЕЧОВИХ ДОКАЗІВ ПІД ЧАС КРИМІНАЛЬНОГО ПРОВАДЖЕННЯ - Ковальчук, Сергій Олександрович (SUPREMANCE OF LAW, 2017)
The article is devoted to the research of theoretical and legal problems, related to the verification of material evidences by analysis of each individual evidence, its synthesis and comparison with other available evidences. The content of each of the listed methods of the verification of material evidences is determined. The expediency of improving of the legal regulation of the verification of evidences by supplementing the CPC of Ukraine by a separate article, devoted to defining of the purpose and content of the verification of evidences and the procedure for its implementation, is substantiated.